The Role of Technology and Institutional Transformation (African Journal of Public Administration & Management, 2026)
Ghana’s reforms align with regional trends in Kenya, Rwanda, and South Africa, where strong political leadership and integrated platforms achieve higher citizen satisfaction.Ghana’s interoperability and user-focused approach offer a replicable model for African digital governance, emphasising inclusivity and efficiency.Digital transformation in Ghana’s public sector has modernised governance, improving service delivery, increasing revenue, and enhancing citizen trust.However, long-term success depends on addressing systemic and policy challenges to ensure sustainable and inclusive digital service delivery.Establish a sustainable national digital transformation fund to reduce reliance on donor financing. Expected Outcome: Long-term financial sustainability and continuity of digital reforms.Expand broadband infrastructure and electricity access in rural areas through public-private partnerships. Expected Outcome: Improved digital inclusion and access to public services in rural communities.Develop a comprehensive National Data Governance Framework defining ownership, consent, and accountability. Expected Outcome: Coordinated, ethical, and transparent management of public sector data.